Prevention of Health Risk Factors in Latin America and the Caribbean : Governance of Five Multisectoral Efforts - Bonilla-Chacin, Maria Eugenia (World Bank, Washington, DC, 2014)
Non-communicable diseases (NCDs) represent an important and growing burden to the health and economies of the Latin America and the Caribbean (LAC) region. However, some of this burden can be prevented or controlled through targeted clinical services and multi-sectoral activities aimed at improving diet, promoting physical activity, and reducing tobacco use and alcohol abuse. This study focuses on population-wide, multi-sectoral interventions to prevent risk factors for NCDs. This study seeks to answer the following questions: what is the health and economic burden of NCDs in the region?; what are countries doing to promote healthy living and prevent risk factors for NCDs?; what are the main governance challenges countries face in developing and implementing population-wide NCD prevention interventions and which are the success stories?; and what else can the region do to reduce health risk factors and prevent the onset of NCDs? This study documents governance challenges in the design and implementation of promising or successful population-wide interventions intended to prevent health risk factors in LAC. It focuses on the process whereby public officials develop and implement primary-prevention policies and programs. It is composed of five commissioned case studies on multi-sectoral interventions to promote healthy living in the region. These case studies examine which stakeholders participated directly or indirectly in the decision-making process; what positions they held; which incentives they faced; which strategies they pursued; how did existing institutional arrangements affect the decision-making process; what lessons can be drawn from these processes; and what were the successes and setbacks? This report provides a glimpse into the types of opposing interests and power games involved in proposing, passing, and implementing successful or promising population-based health interventions in LAC. The aim is to provide information on the struggles and challenges involved in the design and implementation of policies, presenting an array of possible instruments and models that can be useful and adaptable to specific scenarios.